Unraveling Particle Formation: From Single Droplet Drying to Spray Drying and Electrospraying - Eline Boel; Robin Koekoekx; Sien Dedroog; Iurii Babkin; Maria Rosaria Vetrano; Christian Clasen; Guy Van den Mooter (MDPI AG, 2020)
Spray drying and electrospraying are well-established drying processes that already have proven their value in the pharmaceutical field. However, there is currently still a lack of knowledge on the fundamentals of the particle formation process, thereby hampering fast and cost-effective particle engineering. To get a better understanding of how functional particles are formed with respect to process and formulation parameters, it is indispensable to offer a comprehensive overview of critical aspects of the droplet drying and particle formation process. This review therefore closely relates single droplet drying to pharmaceutical applications. Although excellent reviews exist of the different aspects, there is, to the best of our knowledge, no single review that describes all steps that one should consider when trying to engineer a certain type of particle morphology. The findings presented in this article have strengthened the predictive value of single droplet drying for pharmaceutical drying applications like spray drying and electrospraying. Continuous follow-up of the particle formation process in single droplet drying experiments hence allows optimization of manufacturing processes and particle engineering approaches and acceleration of process development.